In situ measurement of estrogenic activity in various aquatic systems using organic diffusive gradients in thin-film coupled with ERE-CALUX bioassay. (June 2019) - Guo, Wei; Van Langenhove, Kersten; Vandermarken, Tara; Denison, Michael S.; Elskens, Marc; Baeyens, Willy; Gao, Yue
Abstract: Organic-diffusive gradients in thin-film samplers (o-DGT), were developed and applied for accumulation of estrogen and estrogen-like compounds on a XAD18 resin and deployed in situ in the effluents of Beijing Gaobeidian Wastewater Treatment Plant (GWWTP) and Brussels North Wastewater Treatment Plant as well as in several aquatic systems in Belgium, including the Zenne River, the Belgian Oostende Harbor and the North Sea. Estrogenic compounds accumulate on the XAD18 resin and the estrogenic activity of the resin extract was measured with the Estrogen Responsive Elements-Chemically Activated LUciferase gene eXpression (ERE-CALUX) bioassay. With this result and by applying Fick's diffusion law, it is possible to calculate the estrogenic activity in the aquatic system, if the diffusion boundary layer (DBL) is known or negligible compared to the hydrogel diffusive layer thickness. The DBL thickness in our study varied from 0.010 to 0.023 cm and ignoring the DBL thickness would for instance, underestimate the estrogenic activity by 10–20%. Estrogenic activities in the secondary effluent of GWWTP were the highest (29 ± 4 ng E2-equivalents L −1 ), while the lowest level was found at the Belgian Oostende Harbor (0.05 ± 0.01 ng E2-equivalents L −1 ). Comparable estrogenic activities in water samples measured by o-DGT and grab sampling were obtained, confirming that o-DGT can be efficiently used in various aquatic systems. The advantage of our sampling and measuring method is that very low, time averaged estrogenic activities can be determined, with a minimum of sample treatment. The risk of sample contamination is very low as well as the cost of the whole analytical procedure. Graphical abstract: Unlabelled Image Highlights: DGT combined with ERE-CALUX was used to measure in situ water estrogenic activity. Neglecting the DBL underestimates the estrogenic activity by 10–20%. DGT and grab sampling give comparable results for the estrogenic activity assessment. DGT is better suited for a time-weighted average (TWA) estrogenic activity.